Endothelial injury and decline in lung function in persons living with HIV: a prospective Danish cohort study including 698 adults - Rønn, Christian; Knudsen, Andreas Dehlbæk; Arentoft, Nicoline Stender; Thudium, Rebekka Faber; Heidari, Safura-Luise; Sivapalan, Pradeesh; Ulrik, Charlotte S.; Benfield, Thomas; Ostrowski, Sisse Rye; Jensen, Jens Ulrik Stæhr; Nielsen, Susanne D. (Frontiers in Medicine, 2024)
Objectives Endothelial injury may promote declining lung function. We aimed to investigate in well-treated persons living with HIV (PLWH) whether elevated levels of thrombomodulin (TM) and syndecan-1 (SDC1) are associated with excess lung function decline and worsening dyspnea. Methods A prospective cohort study comprising patients from the Copenhagen municipality. We included 698 PLWH with undetectable viral load. Biomarkers and demographics were measured at baseline, spirometry [forced expiratory volume in one second (FEV1) and forced vital capacity (FVC)] and dyspnea score both at baseline and 2-year follow-up. Both biomarkers were dichotomized at the 3rd quartile. Decline in lung function was estimated using a linear mixed model with patient-specific random effect. Increase in dyspnea score was estimated using a general mixed logistic regression model. Results We did not find an association between elevated SDC1 or TM and an excess decline in neither FEV1: SDC1: 4.5 mL/year (95% CI: −3.9–12.9, p = 0.30), TM: 2.2 mL/year (95% CI: −6.0–10.4, p = 0.60) nor FVC: SDC1: 4.1 mL/year (95% CI: −6.0–14.2, p = 0.42), TM: 1.4 mL/year (95% CI: −8.3–11.1, p = 0.78). A subgroup analysis of never-smokers was consistent with the main analysis. Likewise, we did not find any association between elevated SDC1 and TM and increase in dyspnea score: SDC1: OR 1.43 (95% CI: 0.89–2.30, p = 0.14), TM: OR 1.05 (95% CI: 0.65–1.71, p = 0.26). Conclusion We did not find a significant association between elevated biomarkers of endothelial injury and decline in lung function nor dyspnea.